EFFECTS OF COCOA POWDER ON OXIDANT/ ANTIOXIDANT STATUS IN LIVER, HEART AND KIDNEY TISSUES OF RATS - S. Noori; K. Nasir; T. Mahboob (Journal of Animal and Plant Sciences, 2009)
The aim of study was to asses the oxidative status in terms of lipid peroxidation and antioxidant enzymes in different tissues of orally administered cocoa-treated rats. For this purpose 12 Male Albino Wistar rats were randomly divided into 2 groups; each group consists of 6 rats. Group I remain untreated, comprises healthy rats. Group II received cocoa powder (1g/kg b.w.) orally for 21 consecutive days. Oxidative status was evaluated by Catalase, GSH, SOD, MDA and 4-HNE, in Liver, Heart and Kidney tissues. The cocoa-treated rats showed significantly increased level of GSH in liver and heart tissue, Catalase in liver and heart, SOD in liver, MDA in liver, similarly decreased level of GSH in kidney tissue, 4-Hydroxynonenal (4-HNE) in liver and heart tissues. Body weight was decreased. No mortality was observed at this dose. The results explain the beneficial antioxidant effects and reveal that cocoa powder enhanced the antioxidant enzymes level in liver and heart tissues while no remarkable changes was observed in kidney tissue.
Keywords: Antioxidant enzymes; Cocoa; Oxidative status; Kidney; Liver; Heart.